Biuletyn Informacyjny Międzyzakładowego Komitetu Założycielskiego Niezależnego Samorządnego Związku Zawodowego "Solidarność" Region Środkowo-Wschodni . no. 15, 1981 - [ed. Ewa Kowalska et al.] (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: For trade-union internal use; Publication suspended after introduction of the Martial Law. Republished already on January 22, 1982, with volume numeration continous with the previous edition